The use of lithium (alpha-methylbenzyl)allylamide for the asymmetric synthesis of unsaturated beta-amino acid derivatives - Davies, S; Fenwick, DR; Ichihara, O (1997)
The unsaturated β-amino acid derivatives (3R)-(E)-3-(N-tert- butoxycarbonyl)aminohex-4-enoate and methyl (2S,3S)-3-(N-tert- butoxycarbonyl)-amino-2-bydroxyhex-4-enoate have been synthesised from lithium (s)-(α-methylbenzyl)allylamide and (E,E)-tert-butyl hex-2,4- dienoate. After a highly stereoselective conjugate addition of the lithium amide to the α,β-unsaturated ester, or a highly stereoselective conjugate addition-electrophilic hydroxylation, the adducts are deallylated and the resulting secondary amines converted to either a benzoyl amide or oxazolidinone. The N-α-methylbenzyl group is then removed with either formic acid or using a dissolving metal reduction. These deprotection procedures leave unsaturation in the molecules intact.